Fast Hybrid MPPT Technique for Photovoltaic Applications: Numerical and Experimental Validation. (3rd June 2014) - Aurilio, Gianluca; Balato, Marco; Graditi, Giorgio; Landi, Carmine; Luiso, Mario; Vitelli, Massimo
Abstract : In PV applications, under mismatching conditions, it is necessary to adopt a maximum power point tracking (MPPT) technique which is able to regulate not only the voltages of the PV modules of the array but also the DC input voltage of the inverter. Such a technique can be considered a hybrid MPPT (HMPPT) technique since it is neither only distributed on the PV modules of the PV array or only centralized at the input of the inverter. In this paper a new HMPPT technique is presented and discussed. Its main advantages are the high MPPT efficiency and the high speed of tracking which are obtained by means of a fast estimate of the optimal values of PV modules voltages and of the input inverter voltage. The new HMPPT technique is compared with simple HMPPT techniques based on the scan of the power versus voltage inverter input characteristic. The theoretical analysis and the results of numerical simulations are widely discussed. Moreover, a laboratory test system, equipped with PV emulators, has been realized and used in order to experimentally validate the proposed technique.